2019
DOI: 10.9734/jsrr/2019/v22i530101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thermal Treatment on Anatomical and Mechanical Properties of Ricinodendron heudelotii Wood

Abstract: The study examined the impact of thermal treatment on anatomical and mechanical properties Ricinodendron heudelotii wood. Wood samples were oven dried at 105°C and cooled in a desiccator to a constant weight before the thermal treatment. Heat treatment of wood was carried out in a Furnace at 120°C, 140°C and 160°C for 45 minutes and 90 minutes. The Density, Modulus of Elasticity (MOE), Modulus of Rupture (MOR), and the anatomical properties were assessed. The results for Density of Ricinodendron heudelotii woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…After determining the density and mechanical parameters of all samples, they were divided into 4 groups (of similar mean values), for modification under different temperature variants. Modification was carried out in 4 temperature variants: 140, 160, 180 and 200 • C. These are the temperatures used when modifying wood for testing [14,21], and in industry [15]. By using several variants of the modification temperature, it was possible to determine how the temperature affects the properties of the wood.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After determining the density and mechanical parameters of all samples, they were divided into 4 groups (of similar mean values), for modification under different temperature variants. Modification was carried out in 4 temperature variants: 140, 160, 180 and 200 • C. These are the temperatures used when modifying wood for testing [14,21], and in industry [15]. By using several variants of the modification temperature, it was possible to determine how the temperature affects the properties of the wood.…”
Section: Methodsmentioning
confidence: 99%
“…Absorption occurs when the oil temperature drops after the modification with samples still in the medium, or when the material is extracted from the oil immediately after the modification time. Studies have also shown changes of resonance parameters of wood after biological modification [20] and descriptions of changes in the mechanical parameters of wood after thermal modification in a superheated steam atmosphere [8,14,[21][22][23][24]. However, to date, we have found no study describing the direct impact of OHT modification on the acoustic parameters of resonant wood.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our findings agree with the report of recently published work. 12 Previous studies asserted that the influence of treatment method on anatomical structures of wood varied principally according to the different modifications system. 1,5 Contrarily, another study asserted that different modification system (open and closed system) does not have a significant bearing on anatomical changes.…”
Section: Transmission Light Microscope Observationmentioning
confidence: 99%